REVIEW OF SOME TRADITIONAL HERBALS INCLUDED IN USADA TENUNG TANYA LARA AS DIARRHEA THERAPY AGENTS - Suardiana, I Kadek; Yadnya Putra, A.A Gede Rai (Journal Pharmaceutical Science and Application; Vol 2 No 2 (2020): Journal Pharmaceutical Science and Application, 2020)
Background: Diarrhea is one of the most extraordinary diseases in the world, with a number of 2.195 children die every day, and 801.000 children die from diarrhea every year. Diarrhea therapy has actually been conducted by society, but the use of synthetic drugs is limited for diarrhea cases since it will trigger undesirable effects, such as abdominal pain and resistance to pathogenic bacteria. Bali, with its unique culture, has Usada Tenung Tanya Lara, which contains procedures for treating diarrhea using plants. Objective: This work aimed to review traditional medicine, which is written in Usada Tenung Tanya Lara, that has been intensified nowadays and can be an alternative in the treatment of diarrhea. Methods: This article review using a primary data source and secondary data sources. Result: Some of the plants that have been collected have anti-diarrheal activity in the usada Tenung Tanya Lara are turmeric ( Curcuma longa ), banana ( Musa paradisiaca ) and ancak ( Ficus religiosa ). These three plants mostly have anti-diarrheal activity by inhibiting and killing pathogenic bacteria that cause diarrhea, such as Shigella dysenteriae, Escherichia coli, and Vibrio cholerae . Aside from being antibacterial, all three plants also have several mechanisms to cure diarrhea. Conclusion: It was revealed that turmeric, banana, and ancak leaf could act as agents of diarrhea therapy with their respective mechanisms of actions. Keywords: Diarrhea, Usada Tenung Tanya Lara, Curcuma longa, Musa paradisiaca, Ficus religiosa.